PRIORITIES FOR FORMATION OF EXPORT POTENTIAL OF THE ENTERPRISE - Psiuk , R.M. (The actual problems of regional economy development, 2017)
The peculiarities of export potential formation at domestic industrial enterprises are considered. The key elements of the export potential formation of the industrial enterprise are determined. A blitz analysis of the polymer market in Ukraine was carried out. The directions of the export potential strengthening at the industrial enterprise due to the peculiarities of its invironment functioning are offered.